The effect of properties of human body on statistical characteristics channel on – body communication - Kadhum, Esraa Habeeb; M. AlSabbagh, Haider (Discoveries in Agriculture and Food Sciences, 2014)
In wireless body area networks , on-body radio propagation channels are typically time-varying, because of the frequent body movements , the one case of human body state is statically case when the body is stand up with its hand along the body , the model taking into account the places of nodes as its shown in this paper, the channel characteristics for statistical one case which may birthing can effect on the design ,four channel model line of sight and one sensor (antenna ) put on back which make the channel as non – light of sight .the destine between transmitter and receiver make a very important rule because the path loss dependent on it directly , the system design is many transmitter and one receiver (Master and Slave ) node. single input multi output channel design (SIMO).